Asuhan Keperawatan Pada Ny.M P5ao Post Sectio Caesarea Dengan Indikasi Letak Lintang Di Ruang Anggrek Rsud Surakarta - Pratiwi, Kuswindriani Dwi, Sulastri, S.Kp., M.Kes (2015)
Background:A childbirth is a complex process in order to save of mother and baby. The childbirth with sugery method through abdominal wall (caesare of sugery) more then to be choice when the birthpervaginais dangerous of mother, baby, although both of them or with baby condition have suspicion that across. While condition have suspicion that across if not done immediately it can lead to fetal surgery experience afiksia. Purpose: To knowing a nursing care of client with post section caesarea by suspicion across include assesment, intervention, implementation, and nursing of evalution. Results: After to do of nursing step during 3 days of diagnoses who appear painful, mobilization obstacle, and less of knowledge. Then inside of implementation the part of large is appropriate with plan who use. Conclusion: cooperation between health of team and patient /family is important to success inside nursing of care a patient so the problem of nursing the patient appear painful, mobilization obstacle, and less of knowledge can be implemented properly and some problems can be solved in part to its conclusion. Keywords: caesare of sugery, suspicion that across, risk of anemia